A STUDY OF THE RELATIONSHIP BETWEEN DIET AND OBESITY WITH DENTAL CARIES IN CHILDREN - Arora, A.; Manohar, N.; Scott, Jane A.; Do, L.G.; Bhole, S.; Hayen, A. (2024)
One of the most common infectious diseases related to nutrition is tooth decay. In this study, the relationship between diet and obesity with tooth decay in children was investigated. This descriptive-analytical study was conducted on children. Tooth decay was determined by the DMFT index. Also, BMI (Body Mass Index) was used to evaluate obesity, and a semiquantitative FFQ (Food Frequency Questionnaire) was utilized to evaluate food intake. The results showed that the frequency of caries index in overweight and obese children was significantly higher than in other children (P < 0.05). The results of the frequency of food consumption showed that all children, except for the milk and dairy group, used fruits and vegetables from other food groups. An inverse correlation was observed between tooth decay and the average consumption of milk and dairy products, fruits, and vegetables, and a significant positive correlation was observed between BMI and the frequency of consumption of sweets. In the current study, obesity, consumption of carious snacks, and reduction in consumption of vegetables, fruits, and dairy products have been proposed as risk factors for dental caries in children. Due to the importance of teeth in children's general health, it seems necessary to educate parents and children about following a balanced diet.